Palladium‐Catalyzed Regioselective C−H Arylation of 4‐Azaindazole at C3, C5 and C7 Positions. Issue 16 (19th March 2021) - Faarasse, Soukaina; El Kazzouli, Saïd; Bourzikat, Otmane; Bourg, Stéphane; Aci‐Sèche, Samia; Bonnet, Pascal; Suzenet, Franck; Guillaumet, Gérald
Abstract: Direct and site‐selective C5 and C7 palladium‐catalyzed C−H arylations of 4‐azaindazole N ‐oxide have been achieved. A bidentate ligand and Pd(OAc)2 catalyst in toluene promoted the activation of C5 position, while a phosphine ligand and PdCl2 catalyst in DMA directed the arylation at C7 position. Using this new method, the synthesis of C5, C7‐diarylated 4‐azaindazole N ‐oxides as well as the C3, C5, C7‐triarylated 4‐azaindazoles was achieved towards future medicinal compounds development. Abstract :